Potentially Inappropriate Medication Use in Older People: A Cross-sectional Study Using Beers Criteria - ÖZAYDIN, AYŞE NİLÜFER (My University, 2021)
BACKGROUND: The use of Potentially Inappropriate Medications (PIMs) is common and negatively affects elderly health and disease prognosis. OBJECTIVE: This study aims to analyze the frequency of PIMs in the elderly health records registered to a family health center and to identify risk factors, prescription/nonprescription distribution, distribution by healthcare institutions, number of doctors visits, and health literacy. METHODS: In this cross-sectionalstudy, a stratified sampling method was used to select individuals aged ≥ 65 years. The health records of the participants up to the last 12 months were examined, and medicines used by participants were evaluated according to Beers 2019 criteria. RESULTS: Most of the participants (89.7%, n:183) had PIMs in health records. The mean number of PIMs used by the elderly was 2.9±1.9(min:0, max:8). A positive linear relationship was observed between multimorbidity and the number of PIMs (p=0.001). There was no significant difference in terms of PIMs frequency among healthcare institutions. Prescription and nonprescription PIMs were found to belong to the same drug groups (Pain relievers and stomach medications). A linear and significant correlation was found between the number of PIMs and doctor visits (p=0.047). CONCLUSION: The doctor should examine prescription and over-the-counter medications used by the elderly during the visit. It will be useful to establish a warning system stating that PIMs are available while registering the medications in the electronic system. So, it will be possible for health authorities to re-evaluate the treatment and replace PIMs with rational drug options.
Keywords: doctor-visit; health literacy; non-prescription; pharmacy; PIMs; prescription